Mapeamento das áreas de risco a voçorocamento e caracterização geoambiental da rodovia Am-010 Manaus/Itacoatiara - Am - (:unkn) unknown (Universidade Federal do Amazonas, 2016)
The erosion process comprehension is essential to prevent and conservation of the soil, in this matter the present study has main objective of mapping the Gully–type erosion incisions and the geo-environmental characterization of the Road- AM-010, which connect Manus to the municipalities of Rio Preto da Eva and Itacoatiara. Having the following specifics objectives: Map and quantify of the gullies during the course of the road AM-010; identify the morphology and morphometry (width, length and depth) of the gullies and erosion features, evolution and growth rate, emphasizing the slope characteristics; identify the capacity of infiltrations and the soil resistance to penetration; describe the geo environmental aspects through the road. The methodological procedures were divided in: bibliography review, fieldwork and data analyze. To characterize the slopes, were observed shape, gradient and orientation. The techniques consisted in observations in loco, notes at cadastral file, use of compass, measuring tape and sketching. It was use parameters to estimate the size and risk scale. The infiltrometer was used to measure the infiltration rate and penetromter the measure the soil resistance to penetration. The results show the mapping of 15 gullies though the road AM-010, showing that the gully located at the km 135 has the greatest length (227,5 m), the greatest width is located at the km 104 (24 m) and greatest depth (9 m) at the km 125. The incision that showed the higest infiltration rate is located at the km 137 (15) and the lowest rate was gullies no5 (km 116), regarding the soil resistance the incision that showed the most compacted surface was the incision no5 (km 116), when associated to results of the infiltration test indicate a compacted surface, allowing the runoff. The occurrence of the incisions is connected to the infrastructure construction (paving and pluvial drainage), as well to the geomorphology. The sections that have concentration of gullies as sections that do not obey the local geomorphology.
Keywords: Rodovia AM-010; Voçoroca; Geoambiente; Road AM-010; Gullies; Geoenvironmental; CIÊNCIAS HUMANAS: GEOGRAFIA